A Sosialisasi dan Internalisasi Nilai-Nilai Anti Kekerasan dan Bullying di Lingkungan Kampus bagi Mahasiswa Baru - Fikstif Donal Lintong; Ricky Engel Mawara; Kulyasin (Universitas Cenderawasih, 2025)
This Community Service Community Service activity aims to socialize and internalize the values of anti-violence and bullying to new PPKn FKIP UNCEN students as part of the formation of good citizens. The activity was carried out during the PKKMB period of the 2025/2026 academic year using interactive lectures, group discussions, simulations, and educational video screenings. The pretest and posttest results showed that there was an increase in understanding from a score of 68 to 82. In conclusion, this activity is useful in increasing students' understanding of the importance of a safe and violence-free campus environment.